Expressive Vocabulary Predicts Nonverbal Executive Function: A 2‐year Longitudinal Study of Deaf and Hearing Children. Issue 2 (11th February 2019) - Jones, Anna; Atkinson, Joanna; Marshall, Chloe; Botting, Nicola; St Clair, Michelle C.; Morgan, Gary
Abstract : Numerous studies suggest an association between language and executive function (EF), but evidence of a developmental relationship remains inconclusive. Data were collected from 75 deaf/hard‐of‐hearing (DHH) children and 82 hearing age‐matched controls. Children were 6–11 years old at first time of testing and completed a battery of nonverbal EF tasks and a test of expressive vocabulary. These tasks were completed again 2 years later. Both groups improved their scores on all tasks over this period. DHH children performed significantly less well than hearing peers on some EF tasks and the vocabulary test at both time points. Cross‐lagged panel models showed that vocabulary at Time 1 predicted change in EF scores for both DHH and hearing children but not the reverse.